2020
DOI: 10.1080/14789949.2020.1807584
|View full text |Cite
|
Sign up to set email alerts
|

Prison staff’s views and understanding of the role of emotions in prisoner suicide and violence

Abstract: Suicide and violence are a major concern in prisons, and it has been suggested that alexithymia may be associated with these behaviours. Alexithymia can be defined as the inability to identify and describe emotions. This study aimed to explore staff's understanding and attitudes about identifying and discussing emotions in prisoner suicide and violence. Twenty prison staff across departments were interviewed about their understanding of how emotional difficulties contribute towards prisoner suicide and violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…Previous research has also identified an interplay between individual factors such as difficulties identifying, understanding and expressing emotions with contextual factors such as prison norms, lack of opportunity and permission and toxic masculinity (17). This reflects previous literature which has found that, for instance, self-harm is related to intrapersonal difficulties such as alexithymia, depression and lower resilience as well as external factors such as bullying (76).…”
Section: Individual and Contextual Factorssupporting
confidence: 75%
See 4 more Smart Citations
“…Previous research has also identified an interplay between individual factors such as difficulties identifying, understanding and expressing emotions with contextual factors such as prison norms, lack of opportunity and permission and toxic masculinity (17). This reflects previous literature which has found that, for instance, self-harm is related to intrapersonal difficulties such as alexithymia, depression and lower resilience as well as external factors such as bullying (76).…”
Section: Individual and Contextual Factorssupporting
confidence: 75%
“…This finding has been echoed by others who found that although prisoners are generally unlikely to share emotions with others, there tends to exist a small network of people that they are willing to discuss their emotions with ( 16 , 25 , 29 , 31 ). Although not evidenced in the current study, previous research has reported staff to hold a perception that prisoners would be more likely to discuss their emotions with particular staff members such as female staff and non-uniformed staff ( 17 ).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations